2014
DOI: 10.1101/gr.165837.113
|View full text |Cite
|
Sign up to set email alerts
|

A long-term demasculinization of X-linked intergenic noncoding RNAs in Drosophila melanogaster

Abstract: Recent studies have revealed key roles of noncoding RNAs in sex-related pathways, but little is known about the evolutionary forces acting on these noncoding RNAs. Profiling the transcriptome of Drosophila melanogaster with whole-genome tiling arrays found that 15% of male-biased transcribed fragments are intergenic noncoding RNAs (incRNAs), suggesting a potentially important role for incRNAs in sex-related biological processes. Statistical analysis revealed a paucity of malebiased incRNAs and coding genes on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 53 publications
1
29
1
Order By: Relevance
“…As an interesting contrast to our finding of Y-linked genes with male-limited expression, Baker et al [42] found genes only expressed in males to be enriched on the X chromosome of stalk-eyed flies. Their result seems more surprising than ours, and runs counter to the feminization (or demasculization) of expression patterns of X-linked genes reported in other studies [43][44][45]. Nevertheless, it is unclear how often we ought to expect genes with male-limited expression to be on the Y chromosome.…”
Section: Identification Of Y-linked Markerscontrasting
confidence: 99%
“…As an interesting contrast to our finding of Y-linked genes with male-limited expression, Baker et al [42] found genes only expressed in males to be enriched on the X chromosome of stalk-eyed flies. Their result seems more surprising than ours, and runs counter to the feminization (or demasculization) of expression patterns of X-linked genes reported in other studies [43][44][45]. Nevertheless, it is unclear how often we ought to expect genes with male-limited expression to be on the Y chromosome.…”
Section: Identification Of Y-linked Markerscontrasting
confidence: 99%
“…Older male-biased genes are underrepresented on the Drosophila X chromosome, while younger male-biased genes [those emerged after the melanogaster split 3-6 million years ago (Russo et al 1995)] are enriched (Zhang et al 2010). This suggests that X demasculinization is an evolutionary process (Gao et al 2014). While enrichment of female-biased genes on the X is predicted, demasculinization of the X opposes the expectation that malebenefitting genes should accumulate on the X chromosome (Rice 1984).…”
mentioning
confidence: 50%
“…A study in Drosophila revealed that a large proportion of intergenic regions encode ncRNAs and that particularly early stages of development express most abundant species of ncRNAs [86] . A recent study showed that in Drosophila many of these long ncRNAs are male-biased and preferentially associate with autosomes [87] . In the lepidopteran species Bombyx mori , a W-linked long non-coding RNA has been even implicated in acting as the primary signal in sex determination [57] .…”
Section: Resultsmentioning
confidence: 99%